'Artemisinin Resistance': Something New or Old? Something of a Misnomer?. Issue 9 (September 2020) - Wellems, Thomas E.; Sá, Juliana M.; Su, Xin-zhuan; Connelly, Sean V.; Ellis, Angela C.
Abstract : Artemisinin and its derivatives (ART) are crucial first-line antimalarial drugs that rapidly clear parasitemia, but recrudescences of the infection frequently follow ART monotherapy. For this reason, ART must be used in combination with one or more partner drugs that ensure complete cure. The ability of malaria parasites to survive ART monotherapy may relate to an innate growth bistability phenomenon whereby a fraction of the drug-exposed population enters into metabolic quiescence (dormancy) as persister forms. Characterization of the events that underlie entry and waking from persistence may lead to lasting breakthroughs in malaria chemotherapy that can prevent recrudescences and protect the future of ART-based combination therapies. Highlights: Artemisinin treatment clears malaria parasitemia rapidly but is frequently followed by recrudescent infection unless the artemisinin (or artemisinin derivative) is combined with an effective partner drug. Recrudescence was identified as RI type artemisinin resistance in 1984, when artemisinin-based combination therapy (ACT) was also proposed. RI type artemisinin resistance is innate to Plasmodium falciparum and has not progressed to higher levels (RII or RIII), despite decades of ACT distributions and partner drug failures. Recrudescences from persisters are not associated with parasite clearance times after artemisinin treatment. Persistence as a survival mechanism is distinct from drug resistance acquired by genetic mutations, a distinction that is at risk of being lost when persisters are incorrectly distinguished as 'the drug-resistant parasites'. Understanding and targeting persisters may suggest strategies for lasting breakthroughs in malaria chemotherapy.